The Impact of Different Parental Figures of Adolescents Living With HIV: An Evaluation of Family Structures, Perceived HIV Related Stigma, and Opportunities for Social Support - Wowolo, Gloria; Cao, Wangnan; Bosomtwe, Dennis; Enimil, Anthony; Tarantino, Nicholas; Barker, David H.; Galárraga, Omar (Frontiers in Public Health, 2022)
Although antiretroviral therapy (ART) has changed the expected health outcomes for HIV, there are still issues related to stigma, how people living with HIV are perceived, and the availability of social support. The purpose of this study was to explore the associations between family structure and psychosocial wellbeing reflected by perceived HIV stigma and social support among adolescents living with HIV in Kumasi, Ghana. This paper used baseline data from two mixed methods studies that evaluated the safety and preliminary efficacy of group-based support programs for ART adherence improvement among adolescents living in Kumasi, Ghana (N=70, aged 12-18 years). A multivariate linear regression analysis was employed to examine the associations between family structure and the outcomes of stigma and social support. The main variables for family structure were single mothers and female caregivers. We found that single motherhood was a significant determinant of stigma. When compared to other categories of caregiver types, adolescents being raised by their single mothers was associated with a 0.259 decrease in the mean internal HIV stigma score (p=0.029). Also, for female adolescents, being raised by a female guardian (e.g. mother, aunt, grandmother, sister) was associated with a 20.92 point increase in the overall support index (p=0.005). This study shows that the type of parent or guardian, and their gender, influences the perceived stigma and available social support among adolescents living with HIV in Ghana. Vulnerable subgroups of adolescents living with HIV, particularly those raised up by male caregivers, should be provided with additional support.